Jesus in Arabia: Tracing the Spread of Christianity into the Desert - Al-Jallad, Ahmad (Biblical archaeology review, 2022)
Our project may have found the earliest reference to Christian belief among the ancient Arabs. Likely dating to the fourth century, a desert inscription written in a peculiar script appears to invoke the name of Jesus. What does this unique text reveal about Christianity’s first spread to the Arabian tribes?